A new species of Cyclopogon (Orchidaceae: Spiranthinae) from Southwestern Ecuador: Cyclopogon soniae-juaniorum - Zambrano Romero, Bosco Javier; Solano, Rodolfo (Phytotaxa, 2018)
The most species-rich genus of Spiranthinae Lindley (1840: 441, 462) is Cyclopogon Presl (1827: 93) with 83 species (Chase et al. 2015). It is distributed from Florida to northern Argentina and southern Brazil, including the Antilles, but the greatest species richness is found in Brazil and the Andean regions of Colombia, Ecuador, Peru and Bolivia. One species, Cyclopogon obliquus (Smith 1910: 74) Szlachetko (1994: 425) has been reported as naturalised in Southeast Asia (Salazar 2003).